OC-106 Seronegative villous atrophy—coeliac disease just half the time?. (28th May 2012) - Aziz, I; Evans, K E; Cross, S S; Sanders, D S
Abstract : Introduction: Villous atrophy (VA) in the presence of a positive coeliac serology (endomysial [EMA] and tissue transglutaminase [tTG] antibodies) is highly predictive of coeliac disease (CD). However, diagnostic challenges may arise in those where VA is associated with a negative coeliac serology. Aims: To study the aetiology of seronegative VA. Methods: One hundred patients presenting with seronegative VA (both EMA negative and tTG normal range) were prospectively and systematically investigated for CD and other known associations of VA. The history, immunoglobulins and histopathology were initially reviewed, followed if necessary by a combination of HLA typing, gluten challenge, repeat coeliac serology & duodenal biopsies, and exclusion of infection/inflammatory bowel disease. Results: 59 women, 41 men, age range 16–92 years, median age 49 years. CD was present in 44% of cases, followed by gastrointestinal infections (18%), severe duodenitis (4%), crohn's disease (3%), tuberculosis (2%), HIV (2%), drugs (2%) and haematological disorders (2%). In 23% an association was not found, although the majority normalised their small bowel histology on repeat biopsies (17/23, 74%). Reviewing the case with a specialist gastrointestinal (GI) histopathologist played an important role in up to 9% of cases, in terms of identifying a cause or help tailoring further investigations. All coeliac patients tested for HLA status were as expected positive for DQ2 or DQ8 haplotypes (n 37), in comparison to 22/47 (47%) non-coeliacs (p<0.0001). A non-coeliac diagnosis was significantly more common in asian/african patients or those with clinical symptoms of abdominal pain, weight loss or nausea & vomiting (p<0.05). However, there was no difference in age, gender, baseline biochemistry or haematological blood tests between the two groups. Conclusion: Close collaboration with a specialist GI histopathologist is useful in cases of seronegative VA. A cause will be found in 77% of patients, with CD accounting for almost half of all cases. In the 23% with no apparent cause, reassuringly 74% normalised their histology. The minority with persisting VA of unknown cause remain under active follow-up. The prevalence of a positive HLA in cases deemed to be non-coeliacs was greater than that of 25% as accepted for the general population. Many of these cases were due to gastrointestinal infections or an unknown cause, and subsequently normalised their histology (18/22). A threshold model for CD has recently been proposed and these patients may still belong to this disease spectrum—further work looking for intestinal antibody deposits in this group may shed light on this possibility. Competing interests: None declared.